Aspek Argumentasi Hukum dalam Nota Pembelaan (Pledoi) yang Disusun oleh Penasehat Hukum (International Forum of Researchers and Lecturers, 2025)
The role of a lawyer is very necessary and important in order to help the defendant prepare and submit a defense memorandum (pledoi) from the perspective of legal argumentation which is based on logical and accountable thinking. We will discuss about the issued: how the defense memorandum (pledoi) functions for defendants undergoing the criminal case examination process and How aspect legal argumentation in the defense memorandum (pledoi) prepared by the lawyer. The conclusions obtained are first, the function of the defense memorandum (pledoi) for defendants undergoing the criminal case examination process is as a forum for the defendant to defend himself against the accusations or demands submitted by the public prosecutor and to convince the panel of judges trying the a quo case that the defendant should not be sentenced to justice. or at least punished with the lightest punishment possible. Second, the legal argumentation aspect in the defense memorandum (pledoi) prepared by the lawyer is a clear and logical explanation in the context of defense, rebuttal, and/or refutation of the public prosecutor's accusations and demands based on legal thoughts or views as a result of an interpretation or reasoning. law.